2006
DOI: 10.1093/pcp/pci235
|View full text |Cite
|
Sign up to set email alerts
|

Photoinactivation of Ascorbate Peroxidase in Isolated Tobacco Chloroplasts: Galdieria partita APX Maintains the Electron Flux through the Water–Water Cycle in Transplastomic Tobacco Plants

Abstract: We evaluated the H2O2-scavenging activity of the water-water cycle (WWC) in illuminated intact chloroplasts isolated from tobacco leaves. Illumination under conditions that limited photosynthesis [red light (>640 nm), 250 micromol photons m(-2) s(-1) in the absence of HCO3-] caused chloroplasts to take up O2 and accumulate H2O2. Concomitant with the O2 uptake, both ascorbate peroxidase (APX) and glyceraldehyde 3-phosphate dehydrogenase (GAPDH) lost their activities. However, superoxide dismutase (SOD), monodeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 43 publications
0
23
0
2
Order By: Relevance
“…A UV-visible spectrophotometer (Agilent 8453, CA, USA) was used to determine the absorption of extracts. Superoxide dismutase (SOD; EC 1.15.1.1) was determined by the method of Giannopolitis and Ries (1977), catalase (CAT; EC 1.11.1.6) was determined by the method of Arrigoni et al (1992), peroxidase (POD; EC 1.11.1.7) was determined according to Abeles and Biles (1991), and ascorbate peroxidase (APX; EC 1.11.1.11) was determined by the method of Miyake et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…A UV-visible spectrophotometer (Agilent 8453, CA, USA) was used to determine the absorption of extracts. Superoxide dismutase (SOD; EC 1.15.1.1) was determined by the method of Giannopolitis and Ries (1977), catalase (CAT; EC 1.11.1.6) was determined by the method of Arrigoni et al (1992), peroxidase (POD; EC 1.11.1.7) was determined according to Abeles and Biles (1991), and ascorbate peroxidase (APX; EC 1.11.1.11) was determined by the method of Miyake et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…However, the steady-state level of APx activity was elevated during early light stress (Davletova et al, 2005). Since the activity of sAPx and tAPx is highly sensitive to H 2 O 2 (Asada, 2000;Miyake et al, 2006), it implicates expressional induction of chloroplast APx. In the rimb mutants, the redox shift in the Asc pool (Fig.…”
Section: Defects In Redox-box Regulation Do Not Affect Typical Ros Pamentioning
confidence: 99%
“…APX catalyzes the conversion of H 2 O 2 to water with concomitant oxidation of ascorbate to monodehydroascorbate, thereby playing a pivotal role in the detoxification of ROS under biotic or abiotic stresses (Asada, 2006;Miyake et al, 2006). Extensive research has shown that APX isoenzymes are localized in at least three different subcellular compartments in plant cells, namely, cytosol (cAPX), microbody (mAPX), and chloroplast (Ishikawa & Shigeoka, 2008).…”
mentioning
confidence: 99%